URGENSI KUALITAS PELAYANAN PERPUSTAKAAN PERGURUAN TINGGI - Rhoni Rodin (Universitas Padjadjaran, 2015)
The quality of the library service refers to the needs of users. Therefore, a good service is a service that can meet the needs and wishes of the user. Then a good library is a library which is able to provide services to every pemustaka quickly and accurately. Now the theory that is used in this study among others: service quality, the dimension of the quality of service, the determining factors in the quality of service and supervision. The discussion is a total quality services can be influenced by several factors among others: word of